Parental Structure and Autonomy Support: Keys to Satisfy Adolescent’s Basic Psychological Needs - Ariyanti Abidin, Fitri; Joefiani, Poeti; E. Koesma, Rismijati; R. Siregar, Juke (Opción, 2019)
Self-Determination Theory (SDT) postulate that satisfaction on three basic psychological needs (need for relatedness, need for competence, need for au- tonomy) is essential for adolescent’s well-being. Proximal social context plays a crucial role in satisfying those needs. This study aimed to investigate the possible effect of three parenting dimensions (warmth, structure, autonomy support) to the satisfaction of three basic psychological needs. One thousand two hundred and fifty adolescents age 12-15 years old (boys = 572, girls = 678) from 15 cities in Indonesia participated in this study. Using multiple regres- sion analysis, the result indicated that all three parenting dimensions signif- icantly affected the satisfaction of relatedness and competence needs, while only structure and autonomy support found to be significantly affected the need for autonomy. The developmental characteristics of the adolescent and cultural influence on parenting were discussed to explain those results.